A HAUNTING IN VENICE - Christie, Agatha, 1890-1976; Green, Michael (Screenwriter) (London : HarperCollins Publishers, 2023)
A teenage murder witness is drowned in a tub of apples... At a Hallowe'en party, Joyce -- a hostile thirteen-year-old -- boasts that she once witnessed a murder. When no-one believes her, she storms off home. But within hours her body is found, still in the house, drowned in an apple bobbing tub. That night, Hercule Poirot is called in to find the 'evil presence'. But first he must establish whether he is looking for a murderer or a double-murderer...
"First published as 'Hallowe'en party'"--Title page.
Film tie-in.
Keywords: Poirot, Hercule -- (Fictitious character) -- Fiction; Private investigators -- Belgium -- Fiction; Murder -- Investigation -- Fiction; Halloween -- Fiction; Detective and mystery fiction